Analysis of project management tools to support knowledge management - Clemente, M.; Domingues, L. (Procedia Computer Science, 2023)
Knowledge Management is an essential element for the successful implementation of projects. Due to the temporary nature of the projects and the teams that participate in them, the transfer, integration, and management of knowledge among projects is vital to promote sharing best practices, and to avoid the repetition of previous mistakes, in order to increase the probability of success for the projects and the organization. For this reason, Project Management tools can play a significant role in supporting Knowledge Management. The goal of this paper is to analyze and evaluate the project management tools of the Gartner Leader quadrant (2019 Gartner Magic Quadrant) regarding their potential for the Capture, Storage, Sharing and Application of knowledge, according to the artifacts in the PMBOK [1], and determine which are the best options. Gartner's leader tools were compared to Confluence, referenced as a great choice for knowledge and project document management. For the development of the artifact was used the Design Science Research (DSR) methodology. The application that obtained the highest score was Targetprocess.